THE ROLE OF VIDEO-BASED EXERCISES IN DEVELOPING SPEAKING SKILLS IN FOREIGN LANGUAGE TEACHING - Rakhmonkulova Dilshoda Murodkuziyevna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the effectiveness of video-based exercises in developing speaking skills in foreign language learning. The study highlights how audiovisual materials enhance learners’ communicative competence, pronunciation, and fluency. The paper also discusses methodological approaches to integrating video content into classroom  practice.  The  findings  suggest  that  video-based  instruction  significantly increases students’ motivation and improves their oral communication skills.